Adaptive behaviour deficits in individuals with 3q29 deletion syndrome. - Pollak, R. M.; Burrell, T. L.; Cubells, J. F.; Klaiman, C.; Murphy, M. M.; Saulnier, C. A.; Walker, E. F.; White, S. P.; Mulle, J. G. (Journal of Intellectual Disability Research, 2024)
Background: 3q29 deletion syndrome (3q29del) is associated with a significantly increased risk for neurodevelopmental and neuropsychiatric phenotypes. Mild to moderate intellectual disability (ID) is common in this population, and previous work by our team identified substantial deficits in adaptive behaviour. However, the full profile of adaptive function in 3q29del has not been described nor has it been compared with other genomic syndromes associated with elevated risk for neurodevelopmental and neuropsychiatric phenotypes. Methods: Individuals with 3q29del (n = 32, 62.5% male) were evaluated using the Vineland Adaptive Behaviour Scales, Third Edition, Comprehensive Parent/Caregiver Form (Vineland‐3). We explored the relationship between adaptive behaviour and cognitive function, executive function, and neurodevelopmental and neuropsychiatric comorbidities in our 3q29del study sample, and we compared subjects with 3q29del with published data on fragile X syndrome, 22q11.2 deletion syndrome and 16p11.2 deletion and duplication syndromes. Results: Individuals with 3q29del had global deficits in adaptive behaviour that were not driven by specific weaknesses in any given domain. Individual neurodevelopmental and neuropsychiatric diagnoses had a small effect on adaptive behaviour, and the cumulative number of comorbid diagnoses was significantly negatively associated with Vineland‐3 performance. Both cognitive ability and executive function were significantly associated with adaptive behaviour, and executive function was a better predictor of Vineland‐3 performance than cognitive ability. Finally, the severity of adaptive behaviour deficits in 3q29del was distinct from previously published data on comparable genomic disorders. Conclusions: Individuals with 3q29del have significant deficits in adaptive behaviour, affecting all domains assessed by the Vineland‐3. Executive function is a better predictor of adaptive behaviour than cognitive ability in this population and suggests that interventions targeting executive function may be an effective therapeutic strategy.